2018
DOI: 10.1002/jmri.25949
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in fiber tracts in healthy adult brains: A generalized q‐sampling and connectometry study

Abstract: 2 Technical Efficacy: Stage 2 J. MAGN. RESON. IMAGING 2018;48:369-381.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
2
7
0
Order By: Relevance
“…However, we found that the length of fibers in the ACR, SLF_L, PCR_R, PTR_L, SCC, and PLIC regions increases with age. These results are generally consistent with some other observations obtained in our lab, which show that the fiber lengths in SCC, PCR, and PTR regions increase with age (Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, we found that the length of fibers in the ACR, SLF_L, PCR_R, PTR_L, SCC, and PLIC regions increases with age. These results are generally consistent with some other observations obtained in our lab, which show that the fiber lengths in SCC, PCR, and PTR regions increase with age (Liu et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…ROI regions from the TBSS analyses were imported into the DSI-studio for fiber tracking. As per our previous reports (Liu et al, 2018 ), the fiber tracking parameters were set as follows: FA was 0.15, the step size was 0.47, and the angular threshold was less than 60°. Additionally, tract lengths were restricted to 30–300 mm in length.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most enduring findings from diffusion tensor imaging (DTI) studies across the lifespan is the regionally selective distribution of low fractional anisotropy (FA) in frontal white matter with increasing age (Bennett and Madden, 2014;Bhagat and Beaulieu, 2004;Cox et al, 2016;Head et al, 2004;Madden et al, 2012;Pfefferbaum et al, 2005;Rojkova et al, 2016;Salat et al, 2005;Sexton et al, 2014;Vik et al, 2015;Zhang et al, 2010), a finding thathas been corroborated in non-human primates (Kubicki et al, 2018;Makris et al, 2007). An anteriorto-posterior gradient of fiber integrity, in which anterior fiber bundles are more susceptible to age-related degeneration than posterior fibers, has also been demonstrated in the corpus callosum using a variety of analytic approaches, including region-of-interest (ROI) analysis (Bender et al, 2016b;Madden et al, 2012;O'Sullivan et al, 2001;Pfefferbaum et al, 2005;Pfefferbaum and Sullivan, 2003;Salat et al, 2005;Sexton et al, 2014;Xie et al, 2016), voxel-based approaches (Hsu et al, 2008;Salat et al, 2005;Sexton et al, 2014;Zhang et al, 2010), and tract-based analyses (Bennett et al, 2010;Burzynska et al, 2010;Davis et al, 2009;Fjell et al, 2017;Lebel et al, 2012;Liu et al, 2018;Sala et al, 2012;Sullivan et al, 2001Sullivan et al, , 2010.…”
Section: Introductionmentioning
confidence: 89%
“…Noninvasive approaches to infer axon size and density in the living human brain would be invaluable for understanding the microstructural substrate of age-related degeneration of cerebral white matter. The trends in callosal fiber composition identified on histology are supported by multiple neuroimaging studies that have used diffusion magnetic resonance imaging (MRI) to infer white matter microstructural properties in the aging human brain (Abe et al, 2002;Bender et al, 2016b;Bennett and Madden, 2014;Berman et al, 2018;Bhagat and Beaulieu, 2004;Billiet et al, 2015;Branzoli et al, 2016;Chad et al, 2018;Cox et al, 2016;de Lange et al, 2016;Fjell et al, 2016Fjell et al, , 2017Head et al, 2004;Hsu et al, 2008;Lebel et al, 2010;Liu et al, 2018;Madden et al, 2004;Martensson et al, 2018;Moseley, 2002;Nusbaum et al, 2001;Ota et al, 2006;Pfefferbaum et al, 2000Pfefferbaum et al, , 2005Salat et al, 2005;Serbruyns et al, 2015;Sexton et al, 2014;Storsve et al, 2016;Stricker et al, 2015;Sullivan et al, 2001Wang et al, 2018;Xie et al, 2016;Yeatman et al, 2014). One of the most enduring findings from diffusion tensor imaging (DTI) studies across the lifespan is the regionally selective distribution of low fractional anisotropy (FA) in frontal white matter with increasing age (Bennett and Madden, 2014;Bhagat and Beaulieu, 2004;Cox et al, 2016;…”
Section: Introductionmentioning
confidence: 92%
“…While diffusivity and density results sometimes converge, SDF may be more robust to crossing fibers and partial volume effects. 27 Additionally, density measures have shown increased sensitivity in both healthy aging 28 and clinical populations. 29 Investigations of white matter density in bipolar disorder are scarce, but several studies examined white matter diffusivity (FA and RD) in this population.…”
Section: Introductionmentioning
confidence: 99%